Methylprednisolone modulates intracranial pressure in the brain cellular edema induced by water intoxication - Kozler, P; Marešová, D; Pokorný, J (Physiological research, 2017)
Continuous monitoring of the intracranial pressure (ICP) detects impending intracranial hypertension resulting from the impaired intracranial volume homeostasis, when expanding volume generates pressure increase. In this study, cellular brain edema (CE) was induced in rats by water intoxication (WI). Methylprednisolone (MP) was administered intraperitoneally (i.p.) before the start of CE induction, during the induction and after the induction. ICP was monitored for 60 min within 20 h after the completion of the CE induction by fibreoptic pressure transmitter. In rats with induced CE, ICP was increased (Mean+/-SEM: 14.25+/-2.12) as well as in rats with MP administration before the start of CE induction (10.55+/-1.27). In control rats without CE induction (4.62+/-0.24) as well as in rats with MP applied during CE induction (5.52+/-1.32) and in rats with MP applied after the end of CE induction (6.23+/-0.73) ICP was normal. In the last two groups of rats, though the CE was induced, intracranial volume homeostasis was not impaired, intracranial volume as well as ICP were not increased. It is possible to conclude that methylprednisolone significantly influenced intracranial homeostasis and thus also the ICP values in the model of cellular brain edema.
Keywords: intoxikace vodou; edém mozku; mozek; antiflogistika; krysa rodu Rattus; Brain Edema; Intracranial Pressure; zvířata; potkani Wistar; Rats, Wistar; methylprednisolon; Male; Brain; Water Intoxication; Methylprednisolone; Rats; Anti-Inflammatory Agents; Animals; mužské pohlaví; intrakraniální tlak